Year-round performance assessment of a solar parabolic trough collector under climatic condition of Bhiwani, India: A case study. (December 2015) - Kumar, Devander; Kumar, Sudhir
Highlights: Year-round performance of SPTC under the various climatic conditions is presented. A detailed thermo-optical model for PTC system is developed. A comparison of developed thermal model is done with experimental data of SNL. Developed model is very helpful and effective tool in analyzing the PTC system. Enlightens the importance of mini-level SPTC as a promising system to fulfill the energy demands. Abstract: Solar parabolic trough collector (SPTC) is a well-known solar thermal system applied for solar electric generation. Nowadays, major attention is directed toward improving the performance of solar thermal systems with optimization of solar field production. In this research work, a comprehensive thermo-optical modeling has been proposed to evaluate the performance of a mini-level SPTC considering various heat equilibriums with the environment. Here, receiver wall temperature is considered as the base for modeling. Collector consists of a non-evacuated receiver tube with black paint coating and enveloped with glass cover. Available meteorological data in terms of global and diffuse solar insolations, air temperatures and wind speeds have been used as inputs for performance evaluation of SPTC with horizontal and inclined aperture planes. The validation of the proposed analytical model is justified with existing experimental results and yielded a close agreement. The developed model is successfully applied to a SPTC in order to estimate the through-out year performance characteristics in terms of water temperature rise, heat energy generation, optical and thermal efficiency for the climactic conditions of Bhiwani. The results enlighten that using 0.010 kg/s mass flow rate of water and aperture area of around 1.34 m 2, collector achieved maximum rise in water temperature 11.1 °C and 12.2 °C on horizontal and inclined planes, respectively in the month of April. The uppermost heat energy generation is found to be 2.38 kW h/day in May on horizontal plane, 2.46 kW h/day in April on inclined plane. The maximum optical efficiency is attained as 72.26% and 72.4% on horizontal and an inclined plane respectively. The peak instantaneous thermal efficiency is accomplished as 66.78% in July on horizontal plane, 65.77% in September on inclined plane of collector.